Problems Analysis about Early Corrosion of Contour and Early Surface Coating Spallation of Sheet Metal Parts and Their Solutions - CHEN Ji-xue; CHEN Bo-ming; ZHANG Wen-xiong (Gong-kuang zidonghua, 2011)
In order to solve problems of early corrosion of contour and early surface coating spallation of sheet metal parts, production process of a pitch of body of sheet metal parts of one product was tracked, and influence of techniques of burrs removing and coating on coating quality were analyzed. The analysis result showed that remained burrs is main cause of early corrosion of contour and existing of oxide films is basic cause of early surface coating spallation.